(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Non-carious dental diseases that originate during the pre-eruptive stages of tooth development represent a significant yet often underrecognized group of pathologies in pediatric dentistry. These conditions, including enamel hypoplasia, dental fluorosis, amelogenesis imperfecta, and dentinogenesis imperfecta, are closely associated with disturbances in the highly regulated processes of odontogenesis.